Econometric analysis of the industrial growth determinants in Colombia (2018)
An econometric study is carried out using a panel data model with fixed effects to identify the industrial development determinants in Colombia during the term 2005–2015. The database used in the study corresponds to World Bank and the Colombian state. The determinants of industrial growth identified at the theoretical level that allow the enhancement of productive capacities to face foreign competition in Colombia are: innovation; networks of innovations and knowledge among companies and organizations; the interest rate; the capital-product ratio, the unit labor cost; and the exchange rate. The amount invested in scientific, technological and innovation activities by industrial group is the only variable that is not significant in the model.